Bismuth(III) Alkoxide Catalysts for Ring‐Opening Polymerization of Lactides and ϵ‐Caprolactone. Issue 6 (24th January 2013) - Vuorinen, Sirpa; Lahcini, Mohammed; Hatanpää, Timo; Sundberg, Markku; Leskelä, Markku; Repo, Timo
Abstract Homoleptic bismuth alkoxide complexes, Bi(OR)3 [R = iPr (1), tBu (2), and CMe2iPr (3)], are used as catalysts in the ring‐opening polymerization (ROP) of lactides. In contrast to 1, two bulkier bismuth alkoxides, 2 and 3, show high activity in the ROP of lactides in toluene at 75 °C. Notably, BiIII alkoxides 2 and 3 are more active in lactide ROP than SnII octoate activated with n‐butanol under identical reaction conditions. Bismuth alkoxides 2 and 3 exhibit a living behavior in the ROP of lactides that is demonstrated both in homopolymerization and in a polymerization resumption experiment. Polymerization of rac‐lactide using 2 and 3 yields polylactide with a slight heterotactic bias. In addition, 2 is an efficient initiator for the ROP of ϵ‐caprolactone in bulk at 120 °C. Variation of the monomer‐to‐catalyst ratio yielded poly(ϵ‐caprolactone) with <overline>M</overline>ns up to 120 000 g mol−1 in corrected gel‐permeation chromatography (GPC) data.